2008
DOI: 10.1016/j.ijid.2007.09.018
|View full text |Cite
|
Sign up to set email alerts
|

A study of the enterotoxigenicity of coagulase-negative and coagulase-positive staphylococcal isolates from food poisoning outbreaks in Minas Gerais, Brazil

Abstract: The results from this study demonstrate that coagulase-negative as well as coagulase-positive staphylococci isolated from dairy products are capable of genotypic and phenotypic enterotoxigenicity. Furthermore, these data demonstrate that PCR is a sensitive and specific method for screening outbreak isolates regardless of coagulase expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
0
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 25 publications
3
81
0
10
Order By: Relevance
“…Under other circumstances, some species of coagulase-negative staphylococci can present a medical risk. Some coagulase-negative staphylococci (CNS) may behave as opportunistic pathogens, often introduced by medical devices or colonising exposed wounds (Veras et al 2008;Faria et al 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under other circumstances, some species of coagulase-negative staphylococci can present a medical risk. Some coagulase-negative staphylococci (CNS) may behave as opportunistic pathogens, often introduced by medical devices or colonising exposed wounds (Veras et al 2008;Faria et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Even though CNS opportunistic infections are most of the times regarded as being of environmental origin, the distribution and antibiotic resistance patterns of these organisms in the environment are poorly characterised (Veras et al 2008;Faria et al 2009). …”
Section: Antibiotic Resistance Of Coagulase Negative Staphylococcimentioning
confidence: 99%
“…Staphylococcus are blamed for more than 572 outbreaks from 1999 to 2007 (ANVISA, 2008). Several outbreaks caused by these microorganisms have been reported in the literature (Do Carmo et al, 2002, Colombari et al, 2007Veras et al, 2008), and some of them are linked to dairy products.…”
Section: Resultsmentioning
confidence: 99%
“…Due to this, they have received more attention by both governments and industries when establishing regulations, microbiological specifications, or methods. Despite this, the ability of coagulase negative Staphylococcus (CNS) to produce enterotoxins (VernozyRozand et al, 1996;Udo et al, 1999;Zell et al, 2008) and their association with foodborne disease outbreaks have been reported (Do Carmo et al, 2002;Veras et al, 2008). The presence of CNS in foods is of concern, as they are commonly found in raw material (e.g., as milk) and may be used as starter cultures for production of fermented foods (Zell et al, 2008).…”
mentioning
confidence: 99%
“…Entretanto, há relatos da detecção em alimentos, de linhagens de Staphylococcus coagulase negativo produtores de enterotoxinas. (Lamaita et al, 2005;Rapini et al, 2005;Veras et al, 2008).…”
unclassified